(untitled) (Damascus University Journal for legal sciences, 2022)
Customs dispute has acquired its specificity for two reasons. Firstly, one of the parties to the dispute is the General Customs Directorate, which is a public authority that is entrusted with ensuring the enforcement of the Customs Law, all relevant laws and regulations, and protecting the national economy. Secondly, the public interest has been affected by the violation of the provisions of the customs law in general and damaging the public treasury rights in terms of tariffs and other taxes and fees required by law in particular. In view of this specificity, the Customs Law, which is a special law that regulates the relationship between the General Customs Directorate and other natural and legal persons, has limited in some of its provisions the judge’s discretionary authority in considering the customs dispute in civil terms regarding the origin of the right in dispute and the procedures taken in gaining it.